Extended-Interval Gentamicin Dosing for Pulmonic Tularemia - Tyson Dietrich; Katelynn Garcia; Joe Strain; John Ashurst (Case Reports in Infectious Diseases)
Francisella tularensis is a Gram-negative coccobacillus that is rarely encountered in clinical practice. Patients can present with cutaneous, pulmonary, cardiac, mucous membrane, or gastrointestinal involvement. A clinician should have a heightened suspicion in endemic areas or when outbreaks appear. Diagnosis is achieved through serological testing or polymerase chain reaction assays. Although historically the treatment of choice was streptomycin, gentamicin is now preferred due to its availability and relatively safer side effect profile with extended-interval dosing. Limited published evidence exists on the effectiveness of extended-interval gentamicin for tularemia. This case series describes four patients with pulmonic tularemia successfully treated with extended-interval dosing of gentamicin without treatment failure or relapse.